2023
DOI: 10.3390/brainsci13071032
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the Subdiaphragmatic Vagus Nerve and Its Connection with the Celiac Plexus and the Ovaries in the Female Rat

Abstract: Communication between the ovaries and the central nervous system occurs by peripheral innervation through the celiac plexus, superior ovarian nerve, and ovarian plexus nerve. The vagus nerve is involved in regulating the ovaries, but the neuroanatomical pathway that links them is not clear. Adult female rats were used for gross anatomy, acetylcholinesterase histochemistry, and the immunofluorescence analysis of tyrosine hydroxylase (TH), choline acetyltransferase (ChAT), and tryptophan hydroxylase 2 (TPH). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…Recent studies in rats have shown that ovaries receive communication through the vagus nerve [ 25 ]. The vagus nerve plays a crucial role in transmitting nociceptive information from visceral and somatic pain to the central nervous system [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in rats have shown that ovaries receive communication through the vagus nerve [ 25 ]. The vagus nerve plays a crucial role in transmitting nociceptive information from visceral and somatic pain to the central nervous system [ 26 ].…”
Section: Discussionmentioning
confidence: 99%